NUMBER OF NON COLIFORM AND TOTAL BACTERIA BALI CATTLE IN THE HIGHLANDS AND LOWLANDS IN BALI AFTER BEING GIVEN MINERALS - Pramita, I Dewa Ayu Dwi Pradnya; Besung, I Nengah Kerta; Sampurna, I Putu (Buletin Veteriner Udayana, 2016)
Research has been conducted on the effect of mineral Bali cattle reared in the highlands and lowlands. Respectively of three males bali cattle weight between 200-300 kg given treatment without mineral (control), 2.5 grams of mineral/head/day, five grams of mineral/head/day, and 7.5grams of mineral/head/day in cattle reared in the highlands and the lowlands. Giving mineral conducted every day for 3 months, feces taken and counted the number of bacteria. The calculation of the amount of non-coliform bacteria grown on media eosin Methylen Blue Agar (EMBA), while the total the number of bacteria carried by the method spread in the media Nutrient Agar (NA). Theresults showed mineral administration in the highlands has no effect on the amount of non coliform bacteria and total count in bali cattle. While granting mineral lowland has no effect on the amount of non colifom bacteria but significant effect on the amount of total count.
Keywords: bali cattle; mineral; non coliform and total count bacteria